EFL Students’ Speaking Activities: The Significance of Games in Classroom Context - Fikroni, Moh. Rofid (Journal of Language Intelligence and Culture, 2019)
ABSTRACT The learning process of language teaching seems to be very demanding and complicated, especially for speaking skill. Speaking, alongside with writing, is considered to be productive skill in which it requires students to produce the language in spoken form. The students need to be able to speak the language by considering some aspects of speaking such as fluency and accuracy. In other words, not only the student has to speak correctly, but also it has to be as smooth as possible. Such particular case becomes one of the reasons why it is difficult to master the skill itself. in another case, it has become much more difficult for the students to grasp the speaking material. Moreover, designing a speaking environment for language teaching in classroom context is no difference. Due to the fact that the scope of speaking skill is complex, the students are reluctant to say something or use the language. That is why the English teacher needs to come up with specific plans to teach English as second or foreign language. One of ways to overcome the problem is by implementing game. The nature of game will help the English teacher to develop such amusing and enjoyable atmosphere in the teaching and learning process.